Hallo Effect in the Turnover Intention of Nurses at Hospital "X" - Danuta Adityarini; Andry Andry; M.F Arrozi Adhikara (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Turnover Intention is recognized as the best predictor of actual displacement. As a result of high turnover in nursing can lead to high financial costs, disrupt functional team formation, increase the workload of other nurses, and can reduce the quality of nursing services for patients and have an impact on overall hospital quality. This study aims to provide empirical evidence of the formation of intention to move to nurses who are influenced by job satisfaction, work-family conflict, and appreciation. The research design is quantitative with a type of explanatory causality research using primary data in the form of a questionnaire distributed to 174 people. The sampling technique in this study was carried out with the saturation sampling method. This research uses Structural Equation Modeling (SEM) analysis. The unit of analysis includes individual nurses with cross sectional time horizons. The results obtained are work-family conflict, appreciation, job satisfaction simultaneously affect the intention to move nurses at the "X" hospital. Work-family conflict has a negative effect on job satisfaction. Giving awards has a positive effect on job satisfaction. Job satisfaction gives effect to the formation of the intention to move. Work-family conflict has a positive effect on the formation of the intention to move. The awarding has a negative effect on the formation of nurses' intentions. The research findings show the “hallo effect” causes the actualization obtained by nurses has not been able to increase job satisfaction, resulting in stronger intention to move.